Survival analysis with python - Nag, Avishek (Boca Raton : Taylor and Francis, 2021)
"Survival analysis uses statistics to calculate time to failure. Survival Analysis with Python takes a fresh look at this complex subject by explaining how to use the Python programming language to perform this type of analysis As the subject itself is very mathematical and full of expressions and formulations, the book provides detailed explanations and examines practical implications"--